2021
DOI: 10.1177/15593258211044845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Gamma Radiation and Lipoic Acid on High- Radiation-Dose Induced Rat Brain Injuries

Abstract: Aim This work aims to investigate the possible radio-adaptive mechanisms induced by low-dose (LD) whole-body γ-irradiation alone or combined with alpha-lipoic acid (ALA) administration in modulating high-dose (HD) head irradiation–induced brain injury in rats. Materials and Methods Rats were irradiated with LD (.25 Gy) 24 hours prior HD (20 Gy), and subjected to ALA (100 mg/kg/day) 5 minutes after HD and continued for 10 days. At the end of the experiment, animals were sacrificed and brain samples were dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Moreover, it has been demonstrated that exposure to low doses of ionizing radiation provided resistance to oxidative injuries in different tissues triggered by high-dose radiation, doxorubicin, and snake venom. 7,36,37 Also, low doses intensified the antioxidant, antiapoptotic, and anti-inflammatory effects of exogenous antioxidants administered to rats against liver and testis injuries induced by different toxicants. 13,38,39 As well, the clinical trial recorded by Yu et al showed that low dose radiation-mediated radioadaptive response can alleviate high dose radiation toxicities, improve the short-term efficacy of radiotherapy, and improve the survival of the lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that exposure to low doses of ionizing radiation provided resistance to oxidative injuries in different tissues triggered by high-dose radiation, doxorubicin, and snake venom. 7,36,37 Also, low doses intensified the antioxidant, antiapoptotic, and anti-inflammatory effects of exogenous antioxidants administered to rats against liver and testis injuries induced by different toxicants. 13,38,39 As well, the clinical trial recorded by Yu et al showed that low dose radiation-mediated radioadaptive response can alleviate high dose radiation toxicities, improve the short-term efficacy of radiotherapy, and improve the survival of the lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It can able to cross cell membranes and quench the free radicals through its redox couple, dihydrolipoic acid (DHLA) directly by scavenging excess generation of free radicals or indirectly via maintaining endogenous enzymatic antioxidants such as superoxide dismutase, catalase, glutathione peroxidase or and non-enzymatic antioxidants such as α-tocopherol, ascorbate, glutathione and/or both [96][97][98] . The therapeutic efficacy of LA against several disorders such as diabetic neuropathy, alzheimers disease, cancer, obesity, disorders like schizophernia, and disorders of central nervous system such as multiple sclerosis is gaining importance in the field of biomedicine 36 .…”
Section: Fig 3: Chemical Structure Of Alpha Lipoic Acidmentioning
confidence: 99%